ETHICS STUDY IN NEW MEDIA ADVERTISING - Sugiarto, Sugiarto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The ethics of advertising in traditional mass media still leaves problems and debates, meanwhile, new technologies continue to develop rapidly and the emergence of new media also requires the application of advertising ethics. This article discusses self-regulation, privacy and the helplessness of regulators in several countries facing globalization due to the development of new media. This study uses a descriptive ethical study method by analyzing several journals published in America, Europe, Asia and Africa. The results of the study show that the ethics of advertising in new media is dynamic and complex and requires self-regulation, the need for ethical judges, privacy, reform and regulation for better advertising development and audience convenience.